Die Verständlichkeit von Rechtstexten und interaktionsorientierter Ansatz - Schenderra, Christian (HERMES - Journal of Language and Communication in Business, 2002)
A lack of consent about legal terms and concepts is not just a communication problem, but may also be viewed as a problem of the definition of legal terms and concepts. This paper starts by discussing several reader text models, and goes on to introducing the concept of the open text. This concept helps to analyse contexts in which, apart from texts, the definitions of legal concepts and terms (for example “legal text”, “ legal lan-guage” or “legal comprehensibility”) are generated during complex, dynamic and ideally democratic interactions. A unilateral act of definition does not only assign certain mean-ings, rules of interpretation, or authorisation of executive action to legal terms, but also ademocratic assumptions about political participation. In this constellation, individuals will always be subjected to the intentions of others, namely those who exert all power, influence and control over the very definition of legal key terms and concepts.